Quantum dots and quantum dot based polymer composites - Hanley, Cormac (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
The main aim of this thesis is to develop a range of new nanomaterials and composite materials based on fluorescent semiconducting nanoparticles (quantum dots). The work involves the synthesis and characterisation of various cadmium containing quantum dots (QDs), along with the investigation of interactions of QDs with various species.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.